Sequence analyses of three nuclear ribosomal loci and a mitochondrial locus in cytologically different forms of Thai Anopheles aconitus mosquitoes - Jariyapan N. (2014)
Ribosomal DNA (rDNA) and mitochondrial DNA (mtDNA) of Anopheles aconitus mosquitoes were examined to investigate intra- and inter-species variation amongst the members of the Minimus group of Anopheles subgenus Cellia. Three rDNA loci (ITS1, ITS2 and D3 regions) and a mtDNA locus (cytochrome oxidase II) were analyzed in An. aconitus Form B and Form C collected in Chiang Mai Province, Thailand. The results show that the consensus sequences of the four loci of the two forms are consistent with those of mosquitoes in the genus Anopheles. No intraindividual variation was detected, but intrapopulation variation was present with polymorphic sequences in some forms for each gene examined. The variation rates were approximately 0.15 to 0.8%. These data indicate that An. aconitus Form B and Form C in Chiang Mai, Thailand are conspecific. In this study, the complete ITS1 sequence of An. aconitus is reported for the first time. The region showed a high variation rate (approximately 55%), compared to the closely related species An. minimus C. It is suggested that this rDNA locus may provide sequence information to differentiate the members of the Minimus group of Anopheles subgenus Cellia.